Un simple tas d’os ? Le fonctionnement complexe d’un ossuaire médiéval du cimetière paroissial de l’église Notre-Dame de Boulonge-sur-Mer (Pas-de-Calais) - Olivier Blamangin; Sophie Oudry; Sacha Kacki (Archéologie Médiévale, 2020)
Collection and secondary deposition of bones were common funerary practices in mediaeval burial grounds. However, the resulting accumulations of bones rarely benefit from careful archaeological excavations and thorough studies. The recent excavation of an ossuary pit in the parish cemetery of Notre-Dame de Boulogne-sur-Mer yet shows that this type of archaeological feature cannot be reduced to the mere expression of a pragmatic management of human remains. This pit, well dated from the fourteenth century by radiocarbon, was used for the primary burials of four individuals (three young children, of which two were deposited in coffins, and an adult placed in a prone position), thus testifying to the coexistence of two functions, two “intents” and various “funerary phases” in the functioning of the ossuary. The results lead to questioning the meaning to be given to these atypical practices, which are sometimes encountered on other sites.